2014
DOI: 10.1186/1471-2202-15-23
|View full text |Cite
|
Sign up to set email alerts
|

The punctate localization of rat Eag1 K+channels is conferred by the proximal post-CNBHD region

Abstract: BackgroundIn mammals, Eag K+ channels (KV10) are exclusively expressed in the brain and comprise two isoforms: Eag1 (KV10.1) and Eag2 (KV10.2). Despite their wide presence in various regions of the brain, the functional role of Eag K+ channels remains obscure. Here we address this question by characterizing the subcellular localization of rat Eag1 (rEag1) and rat Eag2 (rEag2) in hippocampal neurons, as well as determining the structural basis underlying their different localization patterns.ResultsImmunofluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…We have previously demonstrated that rEag1 channels are significantly expressed at synapses, wherein rEag1 immunofluorescence signals display a distinct punctate localization pattern1012. Similar punctate patterns were also reported by a different research group using single-particle-tracking techniques to characterize the presynaptic localization of rEag1 channels13.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…We have previously demonstrated that rEag1 channels are significantly expressed at synapses, wherein rEag1 immunofluorescence signals display a distinct punctate localization pattern1012. Similar punctate patterns were also reported by a different research group using single-particle-tracking techniques to characterize the presynaptic localization of rEag1 channels13.…”
Section: Discussionsupporting
confidence: 74%
“…In Drosophila , where Eag1 K + channels were initially identified, mutations in the eag gene result in distinct defects including hyper-excitability of neuromuscular junction and failure in learning courtship conditioning behavior1415, suggesting an important role of Eag1 channels in synaptic transmissions. Consistent with this notion, mammalian Eag1, but not Eag2, is significantly expressed within the synaptic region and displays a distinct punctate localization pattern101213.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…For biochemical characterization, Myc-tagged rEag1 (Myc-rEag1) was co-expressed with either GFP-tagged rEag1 (GFP-rEag1) or FLAG-tagged hErg (FLAG-hErg) in HEK293T cells for the co-immunoprecipitation experiment. Despite the large size of GFP, previous observations from our laboratory indicated that adding the GFP tag fails to significantly affect the assembly and trafficking of Eag subunits (22). Fig.…”
Section: Resultsmentioning
confidence: 84%